2010
DOI: 10.1016/j.compstruc.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of Gauss–Seidel iterations in a partitioned simulation of fluid–structure interaction

Abstract: A stability analysis of Gauss-Seidel coupling iterations for partitioned simulation of fluid-structure interaction is performed for the flow in a flexible tube. In a previous study the inertia of the structure and the interaction between the segments of the structure were not taken into account. It is now demonstrated that especially the structural inertia has a significant effect on the stability of Gauss-Seidel iterations for a certain range of the time step's size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…This observation is consistent with prior stability analyses [24,48,25]. Here, it is demonstrated that the adjoint simulation behaves in the same way.…”
Section: Stabilitysupporting
confidence: 79%
See 4 more Smart Citations
“…This observation is consistent with prior stability analyses [24,48,25]. Here, it is demonstrated that the adjoint simulation behaves in the same way.…”
Section: Stabilitysupporting
confidence: 79%
“…An approximation for the inverse of the Jacobian will lead to convergence of the coupling iterations if it contains the wave numbers in the interface displacement that are unstable during Gauss-Seidel iterations. For the flow in a one-dimensional flexible tube, it has been shown analytically that only a fraction of these wave numbers are unstable [25]. Other problems have shown similar behaviour.…”
Section: Coupling Iterationsmentioning
confidence: 68%
See 3 more Smart Citations